A randomized phase 2 network trial of tivantinib plus cetuximab versus cetuximab in patients with recurrent/metastatic head and neck squamous cell carcinoma. Issue 10 (19th February 2020) - Kochanny, Sara E.; Worden, Francis P.; Adkins, Douglas R.; Lim, Dean W.; Bauman, Julie E.; Wagner, Stephanie A.; Brisson, Ryan J.; Karrison, Theodore G.; Stadler, Walter M.; Vokes, Everett E.; Seiwert, Tanguy Y.
Abstract : Background: MET signaling is a well described mechanism of resistance to anti‐EGFR therapy, and MET overexpression is common in head and neck squamous cell carcinomas (HNSCCs). In the current trial, the authors compared the oral MET inhibitor tivantinib (ARQ197) in combination with cetuximab (the TC arm) versus a control arm that received cetuximab monotherapy (C) in patients with recurrent/metastatic HNSCC. Methods: In total, 78 evaluable patients with cetuximab‐naive, platinum‐refractory HNSCC were enrolled, including 40 on the TC arm and 38 on the C arm (stratified by human papillomavirus [HPV] status). Patients received oral tivantinib 360 mg twice daily and intravenous cetuximab 500 mg/m 2 once every 2 weeks. The primary outcome was the response rate (according to Response Evaluation Criteria in Solid Tumors, version 1.1), and secondary outcomes included progression‐free and overall survival. After patients progressed on the C arm, tivantinib monotherapy was optional. Results: The response rate was 7.5% in the TC arm (N = 3; 1 complete response) and 7.9% in the C arm (N = 3; not significantly different [NS]). The median progression‐free survival in both arms was 4 months (NS), and the median overall survival was 8 months (NS). Both treatments were well tolerated, with a trend toward increased hematologic toxicities in the TC arm (12.5% had grade 3 leukopenia). The response rate in 31 HPV‐positive/p16‐positive patients was 0% in both arms, whereas the response rate in HPV‐negative patients was 12.7% (12.5% in the TC arm and 13% in the C arm). Fifteen patients received tivantinib monotherapy, and no responses were observed. Conclusions: Combined tivantinib plus cetuximab does not significantly improve the response rate or survival compared with cetuximab alone but does increase toxicity in an unselected HNSCC population. Cetuximab responses appear to be limited to patients who have HPV‐negative HNSCC. MET‐aberration–focused trials for HNSCC and the use of higher potency, selective MET inhibitors remain of interest. Abstract : In recurrent/metastatic head and neck squamous cell carcinoma (HNSCC), combined tivantinib and cetuximab did not significantly improve the tumor response rate or overall survival compared with cetuximab alone but increased toxicity. Patients with human papillomavirus‐positive/p16‐positive disease had a 0% response rate within the study, consistent with other reports that EGFR inhibitors appear to be less active in patients who have HPV‐positive/p16‐positive HNSCC.